Guía de conservación del ambiente como recurso metodológico para potenciar la conservación de los suelos y fortalecer el aprendizaje de los impactos ambientales antrópicos que afectan a los mismos en los estudiantes del décimo grado paralelo a del colegio Fernando Suárez Palacio del barrio cardigán de la ciudad de Loja, periodo 2014 – 2015 - Granda Alban, Jenny Gabriela (2018)
Education nowadays requieres teachers to use methodological resources to motivate students so that the teaching and learning process to be improved. Among the resources used for this purpose, are the guidelines for the conservation of the environment, the same as when using a variety of images, colors, text and activities becomes a didactic support for the students learning, so that the present research work, has the purpose to apply a guide of environmental conservation as a methodological resource to enhance the soil conservation. In this context, for the present investigation the following topic is presented, GUIDE OF CONSERVATION OF THE ENVIRONMENT AS A METHODOLOGICAL RESOURCE TO ENHANCE SOIL CONSERVATION AND STRENGTHEN THE LEARNING OF THE ANTHROPIC ENVIRONMENTAL IMPACTS THAT AFFECT THE SOILS IN THE STUDENTS OF THE TENTH PARALLEL GRADE " A "FROM THE SCHOOL " FERNANDO SUÁREZ PALACIO "OF THE CARRIGÁN DISTRICT CITY OF LOJA, PERIOD 2014 - 2015. As general objective has been proposed; To apply a conservation guide of the environment as a methodological resource to enhance soil conservation and strengthen the learning of anthropic environmental impacts that affect them in the students of the tenth grade parallel "A" of the school "Fernando Suárez Palacio" of the neighborhood Carigán City of Loja, academic period 2014-2015. The methods used were the following: analytical, to analyze the information obtained; the synthetic, to synthesize the information obtained from the situation of the object to be investigated; the inductive, to determine the theoretical referents of the investigation; and, the deductive, which was used to determine the conclusions and recommendations. The bibliographic technique and the Pearson correlation were used as techniques; the instruments, the questionnaire and the pre-test-post test. The population correspond to 16 students and 1 school teacher, object of investigation. With the analysis, discussion and interpretation of the obtained data, it was evidenced that the students have little knowledge about the anthropic environmental impacts that affect soils relief; on the other hand, when the teacher administers the classes he does it in a traditional way, theoretical manner and with few motivating resources for learning; 5 which allowed the application of the Environmental Guidelines in the subject after which the Pearson correlation technique was applied and yielded positive results from where it is deduced that the application of the environmental conservation guidebook as the methodological resource, managed to improve student learning about soil conservation